Preponderance of antibiotic-resistant bacteria associated with partially damaged tomato (Solanum lycopersicum L.) obtained from local markets in Southwest Nigeria - Omotayo, Olumide Ekundayo; Faniyi, Fayokemi Blessing; Akinola, Omowumi Temitayo; Oyeku, Oyeshina Gideon (Plant Science Today, 2025)
Ripened tomato fruits tend to rapidly deteriorate after harvest due to the physiological activities of plant hormones and their naturally high-water content, which makes them susceptible to spoilage by microorganisms. This study was therefore carried out to isolate, characterize and identify pathogenic bacteria associated with partially rotten tomato fruits. Partially rotten tomato fruit samples were sourced from local markets in Southwest Nigeria and subjected to bacterial analysis. The level of susceptibility of the bacteria isolates to commonly used ?-lactamase antibiotics was evaluated via the disc diffusion method. The bacterial isolates with the highest resistance to all the antibiotics tested were selected for molecular characterization using 16S rRNA gene profiling. Forty-two bacterial isolates were obtained from the tomato samples, namely Bacillus spp. (26.19%), Klebsiella spp. (16.67%), Serratia spp. (14.29%), Citrobacter spp. (14.29%), Staphylococcus spp. (7.14%), Pseudomonas spp. (4.76%), Micrococcus spp. (4.76%), Enterobacter spp. (4.76%), Providencia sp. (2.38%), Proteus sp. (2.38%) and Salmonella sp. (2.38%). The highest level of antibiotic resistance of the bacterial isolates was against Ciprofloxacin (10 ?g) at 100%, followed by Zinnacef (20 ?g) at 72.77%, while the highest susceptibility was against Streptomycin (30 ?g) at 94.74%. Using phylogenetic analysis of their 16S rRNA gene sequence, three bacteria that were resistant to every single drug tested were identified as Klebsiella pneumoniae, Enterobacter asburiae and Enterobacter cloacae. This study shows that antibiotic-resistant bacteria are present in partially damaged tomatoes; thus, consumption of improperly cooked tomatoes could pose a significant public health risk.